Legal Validity of Authentic Deeds Based on Cyber Notary According to Law Number 2 of 2014 Concerning The Position of A Notary - Putri, Tiara Novita Aisyah; Qotrunnada , Sinta Annisa; Rizqo, Habibah Fatihatur; Athazada, Hais Subaga Athazada; Fahmi, Miqdad Nidhom (Journal of Law, Politic and Humanities, 2024)
The development of information technology has had a significant impact on the field of notarial law, giving rise to the concept of cyber notary as a response to electronic transactions. Law Number 2 of 2014 concerning the Position of Notaries (UUJN) regulates the authority of notaries in dealing with electronic transactions. Notaries have the authority to certify electronic transactions, as regulated in Article 15 paragraph (3) UUJN. However, the legal validity of authentic deeds based on cyber notary is the subject of a complex debate. The research method used is through a normative juridical approach using a statutory approach and literature study. This article analyzes various aspects related to forced takeovers of companies. The research results show that first, the notary's authority to certify electronic transactions allows the adoption of information technology to ensure legal certainty. Notaries can use cyber notary technology to carry out their duties efficiently and responsive to current developments, providing legal certainty in electronic transactions. Second, the validity of the deed made through a cyber notary must meet the authenticity standards regulated by law. Even though technology enables efficiency, the physical presence of a notary in the deed reading process is still important to ensure the validity and correctness of the contents of the deed. The use of a cyber notary in making Partij Deeds becomes more complicated because the process depends on the notary's ability to accurately record the wishes of the parties. Therefore, notary adaptation to advances in information technology requires adjustments to clear rules and guidelines. There needs to be further clarification in the UUJN to regulate the use of cyber notaries in the context of making deeds by notaries to accommodate technical and legal challenges in the current digital era. In this way, legal certainty in electronic transactions can be guaranteed by legal standards recognized by law.